2022
DOI: 10.3390/ijms23126470
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Integrated Single-Cell Whole Transcriptome Analysis Revealed the p-EMT Tumor Cells—CAFs Communication in Oral Squamous Cell Carcinoma

Abstract: Cancer-associated fibroblasts (CAFs) and partial epithelial–mesenchymal transition (p-EMT) tumor cells are closed together and contribute to the tumor progression of oral squamous cell carcinoma (OSCC). In the present study, we deeply analyzed and integrated OSCC single-cell RNA sequencing datasets to define OSCC CAFs and p-EMT subpopulations. We highlighted the cell–cell interaction network of CAFs and p-EMT tumor cells and suggested biomarkers for the diagnosis and prognosis of OSCC during the metastasis con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…In our work, fibroblast cells were identified as CAFs by their high expression of the EMP3 and VIM, which is associated with carcinogenesis. This finding aligns with previous research 27 . The expression of EMP3 and VIM was confirmed in all subsets of fibroblast cells, which were subsequently categorized into nine distinct subclusters based on their differential gene expression profiles.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our work, fibroblast cells were identified as CAFs by their high expression of the EMP3 and VIM, which is associated with carcinogenesis. This finding aligns with previous research 27 . The expression of EMP3 and VIM was confirmed in all subsets of fibroblast cells, which were subsequently categorized into nine distinct subclusters based on their differential gene expression profiles.…”
Section: Discussionsupporting
confidence: 91%
“…Fibroblast cells are indicated by the expression of DCN, myeloid cells by CD14 and CD168, endothelial cells by PECAM1 and TM4SF1, myofibroblast cells by MYL9, T cells by CD3E and CD3D, B cells by CD79A and MS4A1), and plasma cells by IGHG1 (Figure S1A). 27 The cell count was documented in Table S2. The cellular composition of all the specimens displayed a diverse tumor microenvironment, as illustrated in Figure 1C,D.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pelon et al (2020) confirmed that S1 CAFs promoted the migration and epithelial‐mesenchymal transition (EMT) of breast cancer cells via C‐X‐C motif chemokine ligand 12 (CXCL12) and transforming growth factor beta (TGF‐β) signaling, and the S4 subtype enhanced the invasion of cancer cells via NOTCH signaling. Recently, Huynh et al (2022) analyzed single‐cell sequencing data discovered four subtypes of CAFs: one p‐EMT tumor cell population, and cycling tumor cells as well as TNFSF12‐TNFRSF25/TNFRSF12A interactions between CAFs and p‐EMT tumor cells during tumor metastasis. Liu et al (2019) showed these cells mediate the immunosuppressive TME by promoting monocyte recruitment and macrophage differentiation (innate immunomodulatory functions) or modulating CD8 T‐cell function and differentiation (adaptive immune response).…”
Section: Discussionmentioning
confidence: 99%